Ferric Sulfate Versus Calcium-Enriched Mixture Cement in Pulpotomy of Primary Molars: A Randomized Clinical Trial - Fatemeh Sadat Sajadi; Farzaneh Jalali; Mehrnaz Khademi (Association of Support to Oral Health Research (APESB), 2021)
Objective: To evaluate the postoperative pain and clinical and radiographic success of pulpotomized primary molars using two materials, Ferric Sulfate (FS) and Calcium-Enriched Mixture (CEM) cement, over a period of 3 and 6 months. Material and Methods: This randomized clinical trial was conducted on a total of 38 teeth selected from 19 patients aged 3-9 years. FS 15.5% and CEM cement were used as pulpotomy agents. Permanent restorations were Stainless Steel Crowns (SSCs) in both groups. Patients were recalled for follow-up at 3 and 6 months intervals for clinical and radiographic assessment. Postoperative pain was recorded by using Visual Analogue Scale up to ten days following the treatment. The data were statistically analyzed using chi-square test and repeated measures ANOVA. Results: At 6 months, a 100% clinical success rate was observed in the FS and CEM cement groups. The radiographic success rate in the FS group was 94.7%, whereas 100% in the CEM cement group at 6 months. No statistically significant difference was found between the two groups (p>0.05). There was no significant difference in postoperative pain between the teeth that received either FS or CEM cement as pulpotomy agents following the procedure (p>0.05). Conclusion: There were favorable outcomes of FS and CEM cement in pulpotomy of primary molar teeth.